Antifungal ouzo nanoparticles from guar gum propionate. Issue 108 (8th November 2016) - Kundu, Sonia; Abdullah, Md. Farooque; Das, Aatrayee; Basu, Aalok; Halder, Asim; Das, Mousumi; Samanta, Amalesh; Mukherjee, Arup
Abstract : Synthesis of high DS guar gum propionate esters and the formation of self-assembly nanoparticles for fungus contact killing. Abstract : Herein, we report the synthesis of a guar gum propionate ester and the self-assembly formation of nanoparticles following a facile solvent shifting technique. Hofmeister-ion-guided homogeneous phase reactions were applied in guar galactomannan chemistry. A high degree of substitution (DS) was achieved due to an enhanced access to surface hydroxyl groups in the presence of chaotropic Hofmeister ions. The resulting biopolymer was fully characterized using FT-IR, 13 C NMR, XRD, and thermal analysis. SEM and TEM studies confirmed the formation of quasi-spherical self-assembly nanoparticles in water. The nanoparticles expressed widespread antifungal activities due to the particles' dynamics and the presence of surface propionate moieties. The minimum fungicidal concentration (MFC) in Cryptococcus neoformans and Candida albicans were recorded at 500 μg mL −1 . The development of guar gum propionate self-assembly nanoparticles has great potential in biomedical device applications.